O40. The cytogenetic response of human T-lymphocytes to low doses of p(66)/Be neutrons and heterogeneous exposures to 60Co γ-rays. (September 2016) - Beukes, P.; Depuydt, J.; Castelein, E.; Thierens, H.; Vral, A.; Slabbert, J.P.
Abstract : Introduction: Radiological health concerns for individuals exposed to ionizing radiation are governed by both the extent of exposure, as well as the microscopic dose distribution of the radiation modality. Several quantitative biological endpoints have been developed for radiation dose estimation and are employed worldwide. For real world biodosimetry applications, qualitative aspects such as the radiation type and homogeneity of exposure are vital in the decision making process with respect to suitable medical interventions. Materials and methods: Whole blood samples collected from two consenting adults were exposed to 60 Co γ -rays to doses ranging from 1–6 Gy and 0–2 Gy p(66)/Be neutrons. The samples exposed to 60 Co γ -rays were subsequently diluted with un-irradiated blood to yield a series of equivalent total body doses (ETBD) from 0 up to 4 Gy. Dicentric formation frequencies in T-lymphocyte metaphase spreads were enumerated with the aid of a semi-automated image analysis microscopy system. Results: Dicentric formation induction frequencies were used to estimate whole body doses for each sample respectively. Estimated whole body doses where compared to the equivalent total body dose (ETBD) and found to be in agreement (Pearson's ρ 0.97 <  p  < 0.99). Furthermore the distribution of cytogenetic effects amongst cells within each sample was used to calculate dispersion indices. Similarly to heterogeneous exposures, where damage events appear to be grouped in a specific subpopulation of cells, samples exposed to high-LET radiation also align to this trend. The intercellular distribution of dicentric aberrations for heterogeneously exposed samples ( σ 2 / y ¯ ≥ 1.2 ) and high LET neutron samples ( σ 2 / y ¯ ≈ 1.2 ) were found to be over-dispersed assuming a Poisson distribution applies to the induction of dicentric formations in cells. Conclusion: The dispersion parameter proves to be a useful addition to the dicentric chromosome assay to ascertain qualitative aspects of the exposure conditions required for effective population triage for samples analysed with the high throughput automated image analysis system.